PRODUKTIVITAS PERAWATAN SUMUR (STUDI KASUS DI TOTAL E&P INDONESIE) - Muhdi Rizal; Yustiar Gunawan (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
In the upstream oil and gas industry, at plateau production period, well intervention activity is important to maintain the production level. In PT. Total E&P Indonesie, well intervention has contributed approximately 23% average per year of the whole oil and gas production. It is important to evaluate the well intervention productivity for continuously improvement. This research as the case study in PT. Total E&P Indonesie in offshore area by collecting the data of well intervention activities that have been done on 736 wells. Through the set of analysis and Focus Group Discussion (FGD) with experts resulted 12 dominant factors influenced the well intervention productivity in offshore area and well intervention productivity index 70.8 Scfd/USD wellhead in 2016 and 43.9 Scfd/USD wellhead in 2017. And still by Focus Group Discussion (FGD), there are 18 obstacles of the dominant factor and 31 root causes have been identified which is then analized and resulted 9 recommendations of well intervention productivity improvement.